1995
DOI: 10.1111/j.1151-2916.1995.tb08685.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics Model for the Growth of Silicon Carbide by the Reaction of Liquid Silicon with Carbon

Abstract: The kinetics and mechanism of reaction of glassy carbon with a pure silicon melt or a Si + Mo melt were investigated.The results showed that the growth of a continuous reaction-formed S i c layer followed a fourth-power rate law in the temperature range of 1430" to 1510°C. A model that could explain the fourth-power rate law was developed. In this model, an internal electric field was assumed to be set up over the reaction-formed S i c layer through a negative space charge, and then the diffusion of the carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 13 publications
1
55
0
Order By: Relevance
“…The formation of SiC has also been reported to be controlled by the formation of carbon-ion vacancies across the SiC layer. 22 The self-diffusion of carbon in polycrystalline ␤-SiC has been studied by Hon et al 23 and they report values of 841 Ϯ 13.5 and 563 Ϯ 8.7 kJ/mol for lattice and grain boundary diffusion, respectively. The activation energy for the self-diffusion of Si in ␤-SiC is also estimated to be 912 Ϯ 4.8 kJ/mol.…”
Section: (2) Kinetic Analysismentioning
confidence: 99%
“…The formation of SiC has also been reported to be controlled by the formation of carbon-ion vacancies across the SiC layer. 22 The self-diffusion of carbon in polycrystalline ␤-SiC has been studied by Hon et al 23 and they report values of 841 Ϯ 13.5 and 563 Ϯ 8.7 kJ/mol for lattice and grain boundary diffusion, respectively. The activation energy for the self-diffusion of Si in ␤-SiC is also estimated to be 912 Ϯ 4.8 kJ/mol.…”
Section: (2) Kinetic Analysismentioning
confidence: 99%
“…9,37 For the reaction mechanism, conflicting interpretations are available. Some authors reported continuous reaction product layers at the interface between C and Si that appeared to grow by a diffusion-controlled process; 34,35 no such continuous product layer was found by others [38][39][40] and it was suggested that the reaction product quickly spalled owing to volume misfit between SiC and C, leading to an interface-controlled reaction directly between Si and C. The other mechanism suggests repeating steps of dissolution of C in liquid Si followed by precipitation of SiC from supersaturated solution of C in Si, occur as the reaction front moves. [41][42][43][44] The solution-precipitation and interface-controlled mechanisms have similarity with regard to linear dependence of reaction rate on carbon solubility in Si, the C-Si reaction being assumed to be of first order with respect to C concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In fact liquid silicon infiltration (LSI) processing of SiC ceramics, including cellular Si/SiC ceramics, involves two conceptually independent processes of infiltration of liquid Si into channel pores present in the carbonaceous preforms and reaction between incoming Si and C which are not separable in practice at the LSI processing temperatures. 34,35 Capillarity is considered to be the main driving force for liquid infiltration 6,7,34,36 which is also valid in case of penetration of liquid Si into biocarbon preforms. 9,37 For the reaction mechanism, conflicting interpretations are available.…”
Section: Discussionmentioning
confidence: 99%
“…The instant formation of a thin layer of SiC occurred as a consequence of the first contact of carbon with the liquid Si. A time dependent, parabolic or higher order function for the SiC layer growth is controlled by grain boundary diffusion of carbon through the SiC reaction layer (Zollfrank and Sieber 2005;Gern and Kochendörfer 1997;Zhou and Singh 1995). As shown in Fig.…”
Section: Fabrication Of C/sic Composites By Liquid Silicon Infiltrationmentioning
confidence: 99%